Desain Job Crafting Guna Meningkatkan Efektivitas Kinerja Operator Pada PT. “X” - Willy Gooier; I Nyoman Sutapa (Jurnal Titra, 2023)
PT. "X" is an industrial gas company based in Indonesia. PT. "X" operatesfour business lines, including industrial gas production, industrial gas sales, industrial equipment sales, and industrial equipment installation services. The company faces an issue where employees feel that certain tasks or work methods could be simplified to create a more efficient workflow. The problem related to work methods or job descriptions can be addressed by applying job crafting techniques. The goal of job crafting is to modify aspects and perceptions of a job to align it with the needs and preferences of the employees themselves. Therefore, the objective of this research is to identify better and more efficient work methods that can unleash the best potential of the operators/employees. The job crafting design in this study is developed through interviews. The result obtained is the transition from a manual data reporting method for production to a digital method.